MANF Is Neuroprotective in Early Stages of EAE, and Elevated in Spinal White Matter by Treatment With Dexamethasone - Nam, Jinhan; Koppinen, Tapani K.; Voutilainen, Merja H. (Frontiers in Cellular Neuroscience, 2021)
Multiple sclerosis (MS) is a progressive autoimmune disease characterized by T-cell mediated demyelination in central nervous system (CNS). Experimental autoimmune encephalomyelitis (EAE) is a widely used in vivo disease model of MS. Glucocorticoids such as dexamethasone (dex) function as immunosuppressants and are commonly used to treat acute exacerbations of MS. Dex is also often used as a positive control in EAE studies, as it has been shown to promote motor behavior, inhibit immune cell infiltration into the CNS and regulate the activation of glial cell in EAE. This study further validated the effects of intravenously administrated dex by time-dependent fashion in EAE. Dex postponed clinical signs and motor defects in early stages of EAE. Histological analysis revealed that the degeneration of myelin and axons, as well as the infiltration of peripheral immune cells into the white matter of spinal cord was inhibited by dex in early stages of EAE. Additionally, dex-treatment delayed the neuroinflammatory activation of microglia and astrocytes. Furthermore, this study analyzed the expression of the neurotrophic factor mesencephalic astrocyte-derived neurotrophic factor (MANF) in EAE, and the effect of treatment with dex on MANF-expression. We show that in dex-treated EAE mice expression MANF increased within myelinated areas of spinal cord white matter. We also show that intravenous administration with hMANF in EAE mice improved clinical signs and motor behavior in the early stage of EAE. Our report gives insight to the progression of EAE by providing a time-dependent analysis. Moreover, this study investigates the link between MANF and the EAE model, and shows that MANF is a potential drug target for MS.